Membangun Kepatuhan Perpajakan Sejak Dini Melalui Workshop Pengisian SPT PPh Orang Pribadi di SMKN 10 Jakarta - Selvi Selvi; Notika Rahmi; Pebriana Arimbhi (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Tax is the largest source of state income. However, people's compliance with paying taxes is still low. Therefore, tax education is needed early on. The research question in this activity is how to calculate and fill in the Personal Income Tax Return. The method of this activity is by lecture, demonstration and practice of calculating income tax and filling in the Personal Income Tax Return at SMKN 10 Jakarta. Conclusion of this activity Workshop Completion of Personal Income Tax Return can be held well and run smoothly. Participants are able to manually calculate and record the Personal Income Tax Return. The shortcomings are the absence of learning media, namely dummy e-filing to be practiced by participants